Recursos especiais repetitivos: implicações quanto às agências reguladoras - Santos, Rosane Pereira dos (2019)
The purpose of this study is to verify whether the judgment resulting from the judgment of the special appeal by the repetitive method, that is, the precedent coming from such judgment, has binding power, not only for the other organs and members of the Judiciary, but also in relation to the organs of the Public Administration. Thus, after notes on the special appeal - which go through the creation of the Superior Court of Justice and the prediction of the appeal itself from the Federal Constitution of 1988 - and the justifications for the trial by the repetitive technique, it is now verified that the the purpose of this is to ensure that decisions that are isonomic, expeditious and consistent with legal certainty are sufficient to determine the horizontal and vertical linkage of the Judiciary to the content of the precedent and also its influence on the activities carried out by entities of Power the Regulatory Agencies, whose activities constitute a modality of state intervention in the economy.